2013
DOI: 10.1186/1471-2180-13-103
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activities of almond skins on cagA-positive and-negative clinical isolates of Helicobacter pylori

Abstract: BackgroundHelicobacter pylori is known to be a gastric pathogen of humans. Eradication regimens for H. pylori infection have some side effects, compliance problems, relapses, and antibiotic resistance. Therefore, the need for alternative therapies for H. pylori infections is of special interest. We have previously shown that polyphenols from almond skins are active against a range of food-borne pathogens. The aim of this study was to evaluate the antibacterial effects of natural almond skins before and after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 36 publications
2
41
0
Order By: Relevance
“…Webb (Rosaceae), a rich source of nutrients and phytochemicals, are well documented for their biological effects, including anticancer, antiviral, anti-inflammatory, antioxidant, and antimicrobial activities (Amico et al, 2006;Mandalari et al, 2010Mandalari et al, , 2011Takeoka & Dao, 2003). Bisignano et al (2013) prepared polyphenol-rich extracts from natural almond skins and investigated the antimicrobial properties along with pure flavonoid compounds epicatechin, naringenin, and protocatechuic acid against H. pylori strains. Natural almond skin was found to be more effective against H. pylori followed by natural skin DOI: 10.3109/13880209.2014.952837 post gastric digestion and protocatechuic acid, as a pure flavonoid compound.…”
Section: Potentilla Fruticosamentioning
confidence: 99%
“…Webb (Rosaceae), a rich source of nutrients and phytochemicals, are well documented for their biological effects, including anticancer, antiviral, anti-inflammatory, antioxidant, and antimicrobial activities (Amico et al, 2006;Mandalari et al, 2010Mandalari et al, , 2011Takeoka & Dao, 2003). Bisignano et al (2013) prepared polyphenol-rich extracts from natural almond skins and investigated the antimicrobial properties along with pure flavonoid compounds epicatechin, naringenin, and protocatechuic acid against H. pylori strains. Natural almond skin was found to be more effective against H. pylori followed by natural skin DOI: 10.3109/13880209.2014.952837 post gastric digestion and protocatechuic acid, as a pure flavonoid compound.…”
Section: Potentilla Fruticosamentioning
confidence: 99%
“…As a result, several naturally occurring substances have been investigated as potential alternatives for the treatment of H. pylori infection [6568]. For instance, we have recently demonstrated that polyphenolic fractions from almond skin were active against standard strains and clinical isolates of H. pylori [4]. A recent investigation reported the potential use of several medicinal herbs for the treatment of H. pylori and its complications [69].…”
Section: Helicobacter Pylori Infectionmentioning
confidence: 99%
“…A >3log 10 difference in colony-forming unit (CFU) between BJ 1.25% and BJ 20.0% with H. pylori ATCC 49503 was achieved after 2 h, whereas complete killing was achieved with BJ (10% and 20%) after 8 h and with BJ (5%) after 24 h. BJ gave less killing against H. pylori ATCC 43504, with a complete bacterial killing after 6 h exposure (20% BJ). This outcome could be explained by the increased antibiotic resistance of H. pylori ATCC 43504 compared to H. pylori ATCC 49503 [4]. In the combination assays, the association of BJ with the reference antibiotics determined a reduction of >6log 10 for H. pylori ATCC 49503 after 8 h and for H. pylori ATCC 43504 after 24 h exposure to BJ.…”
Section: Effect Of Citrus Fruits and Their Derivatives Against Helmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies revealed that under in vitro conditions irrespective of genotype status, polyphenols extracted from almond skins were effective against H. pylori, and hence can be administered in combination with antibiotics as a novel strategy for antibiotic resistance (Bisignano et al, 2013). Further, Palacios-Espinosa and his coworkers (2014) demonstrated that Cuphea aequipetala possesses some anti-inflammatory, gastroprotective, and antibacterial properties, required for the treatment of bacterial or nonbacterial GU and symbolizes a significant source for the isolation of anti-H. pylori compounds.…”
Section: Production Of Polyphenolsmentioning
confidence: 99%